Pertimbangan Strategis Jepang dalam Perang Dagang dengan Korea Selatan (2019–2023) - Adibah, Rafiqah; Afriani Sinulingga, Anita; Cory, Silvi (Palito, 2025)
Trade war between Japan and South Korea since 2019 highlights economic tensions triggered by historical and political issues as well as strategic interests in the technology sector. This conflict originated from the South Korean Supreme Court’s decision demanding compensation from Japanese companies for forced labor practices during World War II. In response, Japan implemented export restrictions on semiconductor materials, impacting South Korea’s technology industry. This study aims to analyze Japan’s national interests in this trade war used the concept of national interest by Charles Chong-Han Wu. This study using a qualitative approach and a descriptive-analytical type of research. The findings indicate that Japan seeks to maintain its economic control through dominance in the semiconductor sector and secure its strategic position in the global market. Additionally, the export restrictions are seen as a measure to protect Japan’s national security within the context of technological competition. In conclusion, this trade war reflects the fragile economic interdependence between the two countries and underscores the need for more stable diplomatic strategies. Keywords: Japan, National Interest, Semiconductor, South Korea, Trade War